Borders Unbound: Cultural and Political Borders in Lawrence Osborne’s Beautiful Animals - Mehmet Ali Çelikel (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
Lawrence Osborne’s Beautiful Animals, published in 2017, is the story of two young women holidaying on a Greek Island. The American citizen Samantha and the British citizen Naomi befriend each other during their summer break when they find Faoud, a Syrian refugee washed on the shores of the island. Faoud turns into their summer project. They find him an abandoned home in a village and cherish him with food and drink every day. However, the project fails and they find themselves in a psychologically traumatic adventure that forces them to question the cultural, political and even psychological borders of what they dare to do. This paper focuses on the anxiety of the young women over Faoud’s existence that prompts crucial cultural and political questions. In analysing the novel from the perspective of Sartre’s existentialism, the paper also questions the cultural, political and geographical borders as well as the behavioural and psychological limits of what one can do for self-protection.